Disaster Mitigation in Coastal Areas: Perspective of the Indonesian Spatial Planning Law - Widowati, Dyah Ayu (Jurnal Media Hukum, 2000)
This article is a critical analysis on spatial planning with regard to disaster mitigation in coastal areas. The author explores the concepts and regulations of disaster mitigation and spatial planning in Indonesian coastal areas to identify how spatial planning works in terms of disaster mitigation in coastal areas and the roles of stakeholders in disaster mitigation in coastal areas in the context of the spatial planning law. This normative legal research was conducted by examining secondary data from relevant books, journals, and published documents. This study finds out that, first, according to the Spatial Planning Law, Management of Coastal Zone and Small Islands Law, Disaster Management Law, Job Creation Law, and their derivative regulations, there have been regulations mandating spatial planning as a non-structural mitigative measure with regard to disaster management in coastal areas. Second, in terms of spatial planning and disaster mitigation, the government is the dominant stakeholder, while the role of non-government stakeholders is not expressly provided for which may eventually result in "tokenism" participation in disaster mitigation in coastal areas.